Analisis Dan Perancangan Sistem Informasi Penggajian Pada PT. Tujuh Benua Jambi - Saputra, Sandy; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2021)
PT. Tujuh Benua Jambi that processing salary system data still using microsoft excel. So that problems occur that is poor data storage because they have not yet uses a base data so that took quite some time for especially for their employees salary data, checking their employees salary and who should be investigated over and over on columns that is filled because sometimes an error occurs in the calculation of the employees salary, and the process of the preparation of reports on their employees salary and slip that takes time have to be in relatively a long time because ' one by one employees every month. Hence, this study aims to give solution to the problem by offering information system of employees salary use prototype and used unified model language system like use case diagram, activity diagram, class diagrams and flowchart diagram. The new system produce outputs featuring job data, employee data, bonus data, allowances data, salary data and showing reports required to ease PT. Tujuh Benua Jambi in data processing employess salary. And to advise in implementation system give user to training system first.